Community empowerment in an effort to improve health in the new normal era in Gombong Hamlet, Magelang Regency - Fitriana Yuliastuti; Nurul Umi Salamah; Ashichach Indraswari; Ratfika Nurjanah; Muhammad Kholiq; Athia Fidian; Lintang Muliawanti (Universitas Muhammadiyah Magelang, 2023)
In the new normal era, clean and healthy living practices include always following health protocols like keeping a safe distance, washing hands, and donning masks. This Integrated Community Service Activity aims to increase public knowledge and awareness regarding clean and healthy lifestyles and improve the health and hygiene status. Implementation of this activity is carried out with outreach, training, and mentoring. As a result, more people are aware of the importance of health protocols in the New Normal era, the latest variant of Covid-19 to the therapy needed, how to make hand sanitizer, and an increase in children's knowledge about herbal candies. All activities are expected to be able to enhancing the community's health and standard of living.